Cementless versus Cemented Fixation in Total Knee Arthroplasty - Papas, Paraskevi Vivian; Congiusta, Dominick; Cushner, Fred D. (The Journal of Knee Surgery, 2019)
Despite the success of total knee arthroplasty (TKA), more than 20,000 revision TKA procedures are performed annually. In an effort to decrease failures due to loosening in the past, cementless fixation of TKA was suggested. The preliminary results of cementless fixation for TKA proved to be discouraging, with midterm results linking the use of uncemented components to early aseptic loosening. While cemented TKA has remained the gold standard fixation technique, the changing demographics of the average TKA patient have led some surgeons to revisit cementless fixation as an option.
Keywords: total knee arthropasty; cemented fixation